2016
DOI: 10.31299/hrri.52.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Povezanost samoprocijenjenih simptoma ADHD-a s agresivnim ponašanjem i sudjelovanjem u vršnjačkom nasilju učenika osnovnoškolske dobi

Abstract: Sažetak:Brojna istraživanja potvrdila su povezanost ADHD-a s vršnjačkim nasiljem i agresivnim ponašanjem. Cilj istraživanja bio je provjeriti povezanost različitih samoprocijenjenih simptoma ADHD-a (hiperaktivnost, impulzivnost i nepažnja) s različitim aspektima vršnjačkog nasilja (tjelesno, verbalno i elektroničko) i agresivnim ponašanjem (reaktivna i proaktivna agresija). U istraživanju je sudjelovao 501 učenik 4., 6. i 8. razreda, 50,7% dječaka i 49,3% djevojčica prosječne dobi M=12,72 (sd=1,62). Učenici su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Still, it should be taken into account that the effect size in this case was almost insignificant. As previous studies have shown (McQuade & Hoza, 2015;Velki & Romstein, 2016), a possible explanation for this finding is that symptoms of impulsivity are significant in predicting aggressive behavior or peer violence, which was not included in the scope of the present study. Problems with following the rules, listening to conversations and engaging in group activities that significantly disturb peer relationships are actually a reflection of symptoms of inattention.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Still, it should be taken into account that the effect size in this case was almost insignificant. As previous studies have shown (McQuade & Hoza, 2015;Velki & Romstein, 2016), a possible explanation for this finding is that symptoms of impulsivity are significant in predicting aggressive behavior or peer violence, which was not included in the scope of the present study. Problems with following the rules, listening to conversations and engaging in group activities that significantly disturb peer relationships are actually a reflection of symptoms of inattention.…”
Section: Discussionmentioning
confidence: 87%
“…The symptoms of impulsivity have proved to be particularly challenging for social and emotional functioning of children since these are most often associated with violent and aggressive behavior towards peers (McQuade & Hoza, 2015;Velki & Romstein, 2016). Children that are more impulsive are prone to interrupt others in conversations, to a reckless and ignorant behavior during interaction and, also, a lack of recognition of emotions in others, which results in conflicts during interaction; in other words, they show deficits in verbal behavior and communication skills (Corkum, Corbin, & Pike, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Boys are also four times more often diagnosed with ADHD, especially the impulsive type (Velki, 2012c), and generally express a ower level of empathy (Espelage, Mebane, & Swearer, 2004;Gini, Albiero, Benelli, & Altoè, 2007). Generally, studies have shown that hyperactive children, especially those with significant impulsivity, are more often involved in aggressive behavior and bullying (Velki & Dudaš, 2016;Velki & Romstein, 2016). Impulsive children have a low tolerance to frustration and often react inappropriately (i.e., aggressively) in neutral situations.…”
Section: Resultsmentioning
confidence: 99%